Preparation of low-pressure water softening hollow fiber membranes by polyelectrolyte deposition with two bilayers - Rajabzadeh, Saeid (2014)
The layer-by-layer (LBL) polyelectrolyte deposition was applied on polyethersulfone (PES) hollow fiber ultrafiltration membrane to prepare nanofiltration (NF) membrane for low pressure water softening application for the first time. The effects of polyelectrolyte type and molecular weight (MW), deposited bilayer number, polyelectrolyte solution pH and supporting electrolyte concentration on the performance of resultant membranes were studied thoroughly.